Localized Retinal Nerve Fiber Layer Defects in Red-free Photographs Versus En Face Structural Optical Coherence Tomography Images - Jung, Jae Hoon; Park, Ji-Hye; Yoo, Chungkwon; Kim, Yong Yeon (Journal of glaucoma, 2018)
The purpose of this article is to compare the locations of localized retinal nerve fiber layer (RNFL) defects in red-free fundus photographs and optical coherence tomography (OCT) en face images. We performed a retrospective, comparative study on 46 eyes from 46 glaucoma patients with localized RNFL defects observed in red-free fundus photographs. En face structural images were obtained in the superficial and whole retinal layers using OCT and were overlaid on the corresponding red-free fundus photographs. The proximal/distal angular locations and angular width of each RNFL defect in red-free photos (red-free defects) and in en face structural images (en face defects) were compared. In the superficial retinal layer, there were no significant differences between red-free and en face defects on the proximal/distal angular location and angular width. In the whole retinal layer, the degree of the distal angular location of the en face defects was significantly larger than that of the red-free defects (71.85±18.26 vs. 70.87±17.90 degrees, P=0.003). The correlations of clinical variables with the differences in angular parameters between red-free and en face defects were not significant in the superficial retinal layer. The average RNFL thickness was negatively correlated with the difference in the distal angular location in the whole retinal layer (Pearson correlation coefficient=-0.401, P=0.006). Localized RNFL defects detected in OCT en face structural images of the superficial retinal layer showed high topographic correlation with defects detected in red-free photographs. OCT en face structural images in the superficial layer may be an alternative to red-free fundus photography for the identification of localized RNFL defects in glaucomatous eyes.